Penanganan Kenakalan Remaja Pecandu Napza Dengan Pendidikan Berbasis Kasih Sayang - Azam Syukur Rahmatullah (LITERASI (Jurnal Ilmu Pendidikan), 2013)
This research began when the writer interested to know depply about Suryalaya Islamic Boarding school with “Pondok Remaja Inabah (Islamic  Boarding School “Inabah”) that have succsed handle so many Victims of Narcotics addicted and teenagers/adolescent naughtiness that have applied during many years since 1970.  And recognized by Natioanl and also International. This is so clear that big/great achievement. Obviously Suryalaya Islamic Boarding school with “Pondok Remaja Inabah” is not left even compulsory using love and affection approach for the victims of narcotics addicted.This research is field research located in “Pondok Remaja Inabah XV Putra” or Islamic Boarding School Inabah XV for boys in Suryalaya Islamic Boarding School. The research subject are “abibah” (designation for pupils or students)  took 10 pupils that represent; 3 student that to hesitate, 4 students that honest and  sincere, 4 students that compulsory when the first time come to Islamic Boarding School Inabah XV for boys. Keywords : Education using love